2014
DOI: 10.1900/rds.2014.11.35
|View full text |Cite
|
Sign up to set email alerts
|

Colony-Forming Progenitor Cells in the Postnatal Mouse Liver and Pancreas Give Rise to Morphologically Distinct Insulin-Expressing Colonies in 3D Cultures

Abstract: ■ AbstractIn our previous studies, colony-forming progenitor cells isolated from murine embryonic stem cell-derived cultures were differentiated into morphologically distinct insulinexpressing colonies. These colonies were small and not light-reflective when observed by phase-contrast microscopy (therefore termed "Dark" colonies). A single progenitor cell capable of giving rise to a Dark colony was termed a Dark colony-forming unit (CFU-Dark). The goal of the current study was to test whether endogenous pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…The frequency of CFU-Dark is 0.03% of the total postnatal pancreatic cells and 0.1% of liver cells [24]. In comparison, the PCFUs described in this study comprised at least 1.0% of pancreatic cells (Figs.…”
Section: Figmentioning
confidence: 53%
See 2 more Smart Citations
“…The frequency of CFU-Dark is 0.03% of the total postnatal pancreatic cells and 0.1% of liver cells [24]. In comparison, the PCFUs described in this study comprised at least 1.0% of pancreatic cells (Figs.…”
Section: Figmentioning
confidence: 53%
“…Our colony assays provide quantitative means to characterize self-renewal and differentiation of PCFUs [20]. In a recent publication, we demonstrated that postnatal (1-week-old) liver and pancreas contained CFUDark, a class of rare progenitors that give rise to morphologically distinct insulin-expressing colonies [24]. In addition to Dark colonies, other types of postnatal colonies with cystic or compact structures from pancreas were observed but had not been characterized [24].…”
Section: Onward Ngn3mentioning
confidence: 94%
See 1 more Smart Citation
“…To begin addressing the technical gap in the field of pancreatic progenitor cell biology, colony [7][8][9][10][11] or organoid [12][13][14][15] assays using 3D culture systems were devised. Two colony assays for pancreatic progenitors were developed in our laboratory: one contains a commercial preparation of murine extracellular matrix proteins (ECM) (see Methods and Equipment Table), and the other contains laminin hydrogel, a defined artificial ECM protein [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Two colony assays for pancreatic progenitors were developed in our laboratory: one contains a commercial preparation of murine extracellular matrix proteins (ECM) (see Methods and Equipment Table), and the other contains laminin hydrogel, a defined artificial ECM protein [7][8][9][10][11] . Progenitor cells are mixed in semi-solid medium containing methylcellulose.…”
Section: Introductionmentioning
confidence: 99%